2008
DOI: 10.1089/clo.2007.0066
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Trichostatin A on mRNA Expression of Chromatin Structure-, DNA Methylation-, and Development-Related Genes in Cloned Mouse Blastocysts

Abstract: Trichostatin A (TSA) is the most potent histone deacetylase (HDAC) inhibitor known. We previously reported that treatment of mouse somatic cell nuclear-transferred (SCNT) oocytes with TSA significantly increased the blastocyst rate, blastocyst cell number, and full-term development. How TSA enhances the epigenetic remodeling ability of somatic nuclei and the expression of development-related genes, however, is not known. In the present study, we compared the expression patterns of nine genes involved in chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 54 publications
8
42
1
Order By: Relevance
“…Their dynamic balance regulates gene transcription and gene expression of eukaryotes at the DNA level. Some anomalous expression of HDACs has been observed in SCNT embryos (Suteevun et al 2006;Li et al 2008;Imsoonthornruksa et al 2010;Lee et al 2010). In this study, at the blastocyst stage HDAC2 expression was similar for AMSC-NT embryos and IVF embryos, whereas a lower level was detected in FF-NT embryos.…”
Section: Discussionsupporting
confidence: 51%
“…Their dynamic balance regulates gene transcription and gene expression of eukaryotes at the DNA level. Some anomalous expression of HDACs has been observed in SCNT embryos (Suteevun et al 2006;Li et al 2008;Imsoonthornruksa et al 2010;Lee et al 2010). In this study, at the blastocyst stage HDAC2 expression was similar for AMSC-NT embryos and IVF embryos, whereas a lower level was detected in FF-NT embryos.…”
Section: Discussionsupporting
confidence: 51%
“…TSA treatment of SCNT embryos has been reported to be effective for improving the blastocyst formation rate in mice [20][21][22]38] and pigs [23,24]. In contrast, when bovine SCNT embryos were treated with TSA at 50 nM for 13 h [26] and at 5, 50 or 500 nM for 12 h [25] after NT, no significant effects on the development to the blastocyst stage were observed.…”
Section: Discussionmentioning
confidence: 98%
“…One possible explanation is that HDACi treatment of NT embryos may lead to amendment of abnormal epigenetic modifications, followed by normal expression of some development-related genes. Recent reports have demonstrated that TSA treatment of murine NT embryos influences the expression of genes that regulate chromatin structure and DNA methylation at the blastocyst stage [38] and that the histone acetylation levels of TSA-treated NT embryos are more similar to those of in vitro fertilized embryos than those of untreated cloned embryos in cattle [26]. In addition, Shao et al reported that TSA treatment of mouse SCNT embryos enhances the expression of two embryonic genes shown to be transcriptionally active during zygotic gene activation (ZGA) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one of the reasons for the improved developmental competence of SCNT embryos with TSA treatment may be the access of reprogramming-related factors to nucleosomes. In addition, it has been shown that TSA treatment induces not only histone acetylation but also DNA demethylation [39,40]. In fact, Ding et al [29] suggested that TSA treatment induces a higher level of histone acetylation and lower level of DNA methylation at the 2-cell stage in bovine SCNT embryos, which facilitates epigenetic reprogramming of the transferred somatic cell nucleus.…”
Section: Histone Acetylation Of Miniature Pig Scnt Embryosmentioning
confidence: 99%